THE EFFECT OF INTERPERSONAL COMMUNICATION ON PATIENT SERVICE SATISFACTION IN EMERGENCY DEPARTMENTS DHARMAI CANCER HOSPITAL - Ridho Mohamad Azis; Arvin Hardian (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
The purpose of this study was to determine the extent of the influence of interpersonal communication on patient service satisfaction in the Emergency Department of RS Kanker Dharmais. This research employed a quantitative method, describing the observed phenomena by examining conditions during the processes of data collection, analysis, and data input, using a questionnaire as the main research instrument. The results of the questionnaire, answered by 50 respondents, indicate that the data obtained through appropriate sampling techniques can be considered representative of a particular population. Based on the t-test coefficient table, the calculated t-value for the Interpersonal Communication variable (X) was 0.570, while the t-table value was 1.677. Thus, the calculated t-value was compared with the t-table coefficient value. The significance value was 0.005, which is smaller than 0.05. Interpersonal communication among employees has an influence on increasing patient satisfaction in the Emergency Department of RS Kanker Dharmais. Therefore, employees must be able to maintain service quality and continuously improve their communication skills with others to enhance patient service satisfaction and ensure that patients feel comfortable. Service improvement efforts should specifically focus on enhancing employees’ interpersonal communication skills.